2008
DOI: 10.1177/0002716208322580
|View full text |Cite
|
Sign up to set email alerts
|

The Back Pocket Map: Social Class and Cultural Capital as Transferable Assets in the Advancement of Second-Generation Immigrants

Abstract: In this paper I move beyond current understandings of family-and school-related dynamics that explain the educational and occupational success of low-income immigrant children to investigate the role of cultural capital acquired in the country of origin. Class-related forms of knowledge acquired prior to migration can become invaluable assets in areas of destination through the realization of what Pierre Boutdieu calls habitus, that is, a series of embodied predispositions deployed by individuals in their purs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 25 publications
1
59
0
1
Order By: Relevance
“…However, those who settle and create families on this side of the border should be vigorously assisted, to prevent the realities documented in this paper from reproducing themselves. Additional results, also based on CILS, show that a proactive stance by teachers and counselors and external voluntary support programs can make a significant difference helping poor children of immigrants overcome the handicaps of a negative mode of incorporation (Fernández-Kelly 2008; Haller and Konczal 2008). Active external intervention in support of these families and their aspirations is needed, lest the country’s hunger for cheap labor devolves over time in the emergence of a new underclass.…”
Section: Discussionmentioning
confidence: 99%
“…However, those who settle and create families on this side of the border should be vigorously assisted, to prevent the realities documented in this paper from reproducing themselves. Additional results, also based on CILS, show that a proactive stance by teachers and counselors and external voluntary support programs can make a significant difference helping poor children of immigrants overcome the handicaps of a negative mode of incorporation (Fernández-Kelly 2008; Haller and Konczal 2008). Active external intervention in support of these families and their aspirations is needed, lest the country’s hunger for cheap labor devolves over time in the emergence of a new underclass.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of social groups, other research has examined membership of a religious organization (McNamara & Gonzales, ), identification toward nonheterosexual people (Slootmaeckers & Lievens, ), and sex‐specific behaviors (Silva, ). National character's behavior and custom is examined such as access to education, employment, and familiarity for art among poor families, ethnic minorities, immigrants, and refugees (Fernandez‐Kelly, ; Gaddis, ; Hernandez & Grineski, ; Ovink & Veazey, ; Reese et al., ; Royal, ; Savage & Bennett, ; Slootmaeckers & Lievens, ; Spencer, ; Subiros, ; Weine, Ware, & Klebic, ; van de Werfhorst & Hofstede, ). These rubrics are reproduced through education and lifelong socialization (Gagne et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Homonegativity is a key topic in this research; research has examined homonegativity toward lesbian, gay, bisexual, and transgender individuals (Slootmaeckers & Lievens, ). Sex‐specific groups (Silva, ), immigrants (Fernandez‐Kelly, ; Subiros, ), and refugees (Weine et al., ) have also been examined as specific groups. Nationality represents the dispositions of large groups and communities.…”
Section: Resultsmentioning
confidence: 99%
“…Research has also demonstrated that the attitudes and aspirations of immigrant parents for their children's educational success can affect the motivation and achievement of the children of immigrant parents' parental attitudes and aspirations for their children (van der Veen 2003). The fact that many immigrant parents left their homelands and their friends attests to their aspirations for their children, and many of these immigrant families have cultural capital in the form of helpful contacts on the host country or high career aspirations of their own that help motivate their children to succeed academically (Fernandez-Kelly 2008). Language barriers, uncertainty about how school systems in the host country operate, and cultural differences regarding the perceived role of parents in schools, however, can all serve to limit the involvement of immigrant parents in their children's educational endeavors (Ramirez 2003).…”
Section: The Intersection Of Ethnic Identity and Academic Motivationmentioning
confidence: 99%